Killing me softly. Tre paragrafi e un epilogo sull’insegnamento odierno all’Università - Giancarlo Alfano (Laboratoire Italien)
This essay seeks to interpret the university teaching practices of these last three years by returning digital technologies to their proper cultural and economic framework. The analysis suggests that the move to distance learning poses risks that seem to outweigh the possible benefits.